Factors Affecting The Decision Padang Jaya Farmers, North Bengkulu Regency In Doing Land Function Transfer Irrigation Field To Plantation Crops - Evi Andriani; Rika Dwi Yulihartika (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This study aims to determine the factors that influence the decision to transfer the function of paddy fields to plantation crops and measure, calculate, and predict whether the conversion of agricultural land has an impact on the availability (production) of food, especially rice in the Padang Jaya District, North Bengkulu Regency. . This research was carried out in Padang Jaya District, North Bengkulu Regency from November to December 2021. The method used in this study was a survey method. The method of determining the sample used is simple random sampling. Meanwhile, the selection of village locations was done intentionally (purposive sampling). Data analysis was carried out with Logit Analysis. To test the significance of the parameters in the model, the Likelihood Ratio Test and P-test were used using the Minitab application. The results showed (1) The factors that significantly influenced the decision of farmers to switch the function of paddy fields to plantation crops were the level of formal education, land area, farmers' responses to market dynamics, accessibility of paddy fields to quarterly irrigation, and (2) Transfer of the function of rice fields to plantation crops will have an impact on the availability (production) of food, especially rice, especially in the Padang Jaya district, this can be seen from the rice production in 2008 which was a surplus of 659.19 tons, while in 2009 there was a shortage of 281.34 tons.